An audit of dressing practice by occupational therapists in acute stroke settings in England. (November 2020) - Worthington, Esme; Whitehead, Phillip; Li, Zhaoying; Golding-Day, Miriam; Walker, Marion
Introduction: Dressing independence is commonly affected after stroke, with clinical guidelines recommending that dressing practice should routinely be provided for those with dressing difficulties. The aim of this study was to update the literature on current practice in the treatment of dressing problems in stroke rehabilitation units. Method: A questionnaire survey of occupational therapists experienced in stroke care was sent to 157 stroke units in England. Results: Responses were received from 70 stroke units. Frequency and duration of dressing practice varied substantially between units, with respondents typically providing dressing practice for six to 10 patients per week and spending 30 to 45 minutes per treatment session. Only 17 respondents (24.3%) stated that they regularly used standardised assessments of dressing ability. The functional approach was used more widely than the remedial approach. Service priorities, working environment and limitations of time and staffing were reported to influence dressing practice. Conclusion: There is widespread variability in dressing practice. There is a lack of use of standardised dressing assessments, and therapists' rationale for their choice of approach is unclear.